Never-homozygous genetic variants in healthy populations are potential recessive disease candidates - Schmenger, Torsten; Diwan, Gaurav; Singh, Gurdeep; Apic, Gordana; Russell, Robert B. (npj Genomic Medicine, 2022)
The rapid pace with which genetic variants are now being determined means there is a pressing need to understand how they affect biological systems. Variants from healthy individuals have previously been used to study blood groups or HLA diversity and to identify genes that can apparently be nonfunctional in healthy people. These studies and others have observed a lower than expected frequency of homozygous individuals for potentially deleterious alleles, which would suggest that several of these alleles can lead to recessive disorders. Here we exploited this principle to hunt for potential disease variants in genomes from healthy people. We identified at least 108 exclusively heterozygous variants with evidence for an impact on biological function. We discuss several examples of candidate variants/genes including CCDC8, PANK3, RHD and NLRP12. Overall, the results suggest there are many, comparatively frequent, potentially lethal or disease-causing variants lurking in healthy human populations.
Gesehen am 11.10.2022